2008
DOI: 10.1002/cbf.1489
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of 2‐methoxyestradiol on MCF‐12A and MCF‐7 cell growth, morphology and mitotic spindle formation

Abstract: The influence of 2-methoxyestradiol (2ME) was investigated on cell growth, morphology and spindle formation in a tumorigenic (MCF-7) and non-tumorigenic (MCF-12A) epithelial breast cell line. Inhibition of cell growth was more pronounced in the MCF-7 cells compared to the MCF-12A cells following 2ME treatment. Dose-dependent studies (10 -5 -10 -9 M) revealed that 10 -6 M 2ME inhibited cell growth by 44% in MCF-12A cells and by 84% in MCF-7 cells (P-value < 0.05). 2ME-treated MCF-7 cells showed abnormal metapha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 41 publications
3
35
0
Order By: Relevance
“…Although the use of physiological steroid hormones in experimental studies employs steroid concentrations in the nanomolar range, the metabolite 2-ME 2 is effective in cell free systems at higher concentrations. Previous studies have shown inhibition of cellular proliferation by use of 1 -10 µM 2-ME 2 [Azab et al 2009;LaVallee et al 2002;Mueck and Seeger 2010;Pribluda et al 2000;Van Zijl et al 2008]. Thus the use of 2-ME 2 at the concentrations utilized in our studies is consistent with similar concentrations employed by other investigators in the literature.…”
Section: Resultssupporting
confidence: 89%
“…Although the use of physiological steroid hormones in experimental studies employs steroid concentrations in the nanomolar range, the metabolite 2-ME 2 is effective in cell free systems at higher concentrations. Previous studies have shown inhibition of cellular proliferation by use of 1 -10 µM 2-ME 2 [Azab et al 2009;LaVallee et al 2002;Mueck and Seeger 2010;Pribluda et al 2000;Van Zijl et al 2008]. Thus the use of 2-ME 2 at the concentrations utilized in our studies is consistent with similar concentrations employed by other investigators in the literature.…”
Section: Resultssupporting
confidence: 89%
“…This suggests that these compounds may be able to circumvent drug resistance induced by the activity of PgP efflux pumps [22]. MCF7 and MDA-MB-231 cells were similarly sensitive to the sulphamoylated compounds indicating that these compounds act independently of the estrogen and/or progesterone receptors to induce cell death.…”
Section: Discussionmentioning
confidence: 96%
“…However, at therapeutic doses in vivo, the drug is likely to act by impairing microtubule dynamics (4,5). Given that rapid microtubule dynamics are essential for the correct assembly and function of the mitotic spindle, 2ME2 activates the spindle assembly checkpoint and causes metaphase arrest, and as a consequence, inhibition of cell proliferation and induction of cellular apoptosis (6,7).…”
Section: Introductionmentioning
confidence: 99%